Association Between Regular Use of Gastric Acid Suppressants and Subsequent Risk of Cholelithiasis: A Prospective Cohort Study of 0.47 Million Participants - Man Yang; Man Yang; Man Yang; Bin Xia; Bin Xia; Yawen Lu; Yawen Lu; Qiangsheng He; Qiangsheng He; Yanyan Lin; Ping Yue; Bing Bai; et al. (Frontiers Media S.A., 2022)
Background: Gastric acid suppressants have a major impact on gut microbiome which in turn, may increase the risk of cholelithiasis, but epidemiological evidence remains unclear. We undertook this research to evaluate the association between regular use of proton pump inhibitors (PPIs) and H2-receptor antagonists (H2RAs) with risk of cholelithiasis.Methods: Prospective cohort study included 477,293 UK residents aged 37-73 years from the UK Biobank. We included the participants reported PPI or H2RA use, and were free of cholelithiasis or cancer. We evaluated hazard ratios (HRs) of regular use of PPIs or H2RAs and risk of cholelithiasis adjusting for demographic factors, lifestyle habits, the presence of comorbidities, use of other medications, and clinical indications.Results: We identified 12,870 cases of cholelithiasis over a median follow-up of 8.1 years. Regular use of PPIs (HR 1.22 95% CI 1.16-1.29) or H2RAs (HR 1.16, 95% CI 1.05-1.28) was associated with an increased risk of cholelithiasis after confounding adjustment. There were no major differences among individual PPIs/H2RAs. The absolute risk of PPI-associated cholelithiasis was increased with the baseline predicted risk evaluated by known environmental and genetic risk factors (Risk differences in the lowest vs. the highest quartile: 1.37 vs. 4.29 per 1,000 person-years).Conclusion: Regular use of PPIs and H2RAs was associated with increased risk of cholelithiasis. Future prospective studies are required to confirm whether the observed associations are casual.